A Comparative Study on the Clinical Efficacy of Two Different Disposable Circumcision Suture Devices in Adult Males - Shen, Junwen; Shi, Jihan; Gao, jianguo; Wang, Ning; Tang, Jianer; Yu, Bin; Wang, Weigao; Wang, Rongjiang (Urology Journal, 2017)
Purpose: We evaluated the safety and efficacy of two different kinds of disposable circumcision suture devices in adult men. Materials and Methods: Adult male patients (n = 179; mean age: 23.7 years) with redundant prepuce and/or phimosis were included in a clinical trial from July 2015 to August 2016. Patients were divided into 2 groups: group A using the Langhe disposable circumcision suture device (n = 89), and group B using the Daming disposable circumcision suture device (n = 94). Results: Intraoperative and postoperative bleeding were more serious in the group A of disposable circumcision suture device compared with the group B of disposable circumcision suture device (4.21 ± 1.31 ml) versus (2.56 ± 1.45 ml). Patients in the group B of disposable circumcision suture device had a longer swelling time (group A versus group B: 11.7 ± 0.9 days versus 14.5 ± 1.4 days), the postoperative pain score in the 7 days after surgery (group A versus group B: 2.9 ± 0.9 versus 3.8 ± 1.5), and higher postoperative infection rate (group A versus group B: 4.7% versus 13.8%), the differences were statistically significant (p < 0.05). Conclusion: postoperative complications of the two kinds of disposable circumcision suture devices are different. We should pay attention to the risk of postoperative bleeding when the patients use the Langhe disposable circumcision suture device, while the patients who use the Langhe disposable circumcision suture device will have a longer healing time, and postoperative pain and the risk of infection cannot be ignored after the surgery.